0647 The Relationship Between Amyloid Accumulation And Poor Sleep In Patients With Idiopathic Rem Sleep Behavior Disorder. (12th April 2019) - Lee, Hanul; Joo, Eun Yeon; Seo, Sang Won
Abstract: Introduction: Idiopathic REM sleep behavior disorder (iRBD) is well known as a strong predictor of neurodegeneration, in particular synucleinopathies. Alzheimer's disease (AD) is also reported as a possible development in patients with iRBD, although it is in a limited number of cases and there are concerns about diagnostic accuracy. Amyloid PET scans allow accurate detection of amyloid plaques. The aim of this study is to investigate the clinical and polysomnographic features of iRBD patients depending on amyloid accumulations. Methods: A total of 21 patients with iRBD (mean age 63.6y, 16 male) and age-gender matched 5 controls (mean age 64.4y, 3 male) were enrolled in this study. Diagnosis of iRBD was confirmed by polysomnography. Participants have taken brain MRI, questionnaires (BDI, PSQI, ISI, SSS, ESS), and neuropsychological tests. Results: Currently, 15 iRBD patients and 5 controls completed all studies including amyloid PET scans. Three patients of 15 (20%) had positive amyloid scan while all controls showed negative results. Three iRBD patients with amyloid accumulation (Amy positive) seem to be older than 12 patients without amyloid accumulation (Amy negative) or 5 controls (72.26 vs. 64.54 vs. 64.4, respectively). Disease onset age was 67.0±11.3y in Amy positive and 61.0±6.3y in Amy negative. Mini-Mental State Exam (MMSE) scores looked to be lower in three Amy positive group than Amy negative or controls (24.33±4.0 vs. 28.25±2.0 vs. 27.6±2.5). Neuropsychological tests showed trend of diffuse cognitive dysfunction on all domain in Amy positive group. Patients with Amy positive showed more poor sleep than Amy negative on polysomnography; lower sleep efficiency (58.13±22.35 vs. 83.05±12.02%), more frequent arousal indices (23.93±0.91 vs. 17.95±8.60/h), more N1 sleep (32.06±13.84 vs. 15.57±6.71%) and less N3 sleep (0 vs. 2.42±5.95%). Conclusion: The positive pattern of Amyloid PET scan in iRBD patients seems to indicate, more poor sleep and cognitive decline than patients without amyloid accumulation or controls. Longitudinal studies with more patients and controls are needed to clarify whether amyloid positivity is an early manifestation of AD and its relationship with poor sleep quality. Support (If Any)